Plasma Forming by Spreading of Pulsed Electron Beam in High Pressure Gases; EAPPC with BEAMS and MEGAGAUSS, 2016 Estoril [EAPPC 2016, 6th Euro-Asian Pulsed Power Conference ; BEAMS 2016, 21st International Conference on High-Power Particle Beams ; MG-XV, 15th International Conference on Megagauss Magnetic Field Generation and Rlated Tpics] - Remnev G. E. Gennady Efimovich (2016, 2016)
В фонде НТБ ТПУ отсутствует